Multiple endocrine neoplasia type 1 associated with breast cancer: A case report and review of the literature - JEONG, YOUNG JU (D.A. Spandidos, 2014)
Multiple endocrine neoplasia type 1 (MEN1) is a cancer predisposition syndrome that includes a combination of endocrine and non-endocrine tumors. The present study reports a rare case of MEN1 associated with breast cancer with the MEN1 gene mutation. A 45-year-old female was diagnosed with breast cancer subsequent to presenting with a right breast mass. Pre-operative radiological studies indicated right breast cancer with a suspicious metastatic nodule of the lung. Further studies demonstrated bilateral thyroid nodules, a neuroendocrine tumor of the pancreas, paraganglioma, a left adrenal adenoma, gallstones, uterine subserosal myoma and pituitary macroadenoma. Laboratory examinations revealed hypercalcemia, hypophosphatemia and an increased intact parathyroid hormone level. The workup for the suspected MEN syndrome revealed an increased basal plasma level of insulin-like growth factor-1, prolactin and calcitonin, and an increased 24-h urinary free cortisol level. The patient underwent surgical removal of the breast cancer and the tumors of the pancreas, adrenal gland, thyroid and parathyroid glands, uterus, anterior mediastinum and lung. The pathological diagnosis of the resected breast was of invasive ductal carcinoma. Otherwise the pathological diagnosis was of calcitonin-producing pancreatic endocrine carcinoma, adrenal cortical adenoma, bilateral papillary thyroid carcinomas, parathyroid adenomas, uterine leiomyoma with adenomyosis, a thymic carcinoid tumor and lung hamatoma. Gene analysis was performed to determine the association between gene mutations and the development of tumors in this patient, and a germ-line MEN1 gene mutation was consequently detected. It could be assumed that MEN1 syndrome may have possibly predisposed the present patient to breast cancer. However, additional observations and further studies are required to demonstrate this association.